Current Bancroftian Filariasis Elimination on Thailand-Myanmar Border: Public Health Challenges toward Postgenomic MDA Evaluation. (21st March 2013) - Bhumiratana, Adisak; Intarapuk, Apiradee; Koyadun, Surachart; Maneekan, Pannamas; Sorosjinda-Nunthawarasilp, Prapa
Abstract : From regional and global perspectives, Thailand has progressed toward lymphatic filariasis transmission-free zone in almost entire endemic provinces, being verified by WHO by the end of 2012 after the 5-year implementation of mass drug administration (MDA) with diethylcarbamazine and albendazole as part of the National Program to Eliminate Lymphatic Filariasis (PELF) (2002–2006) and a 4-year expansion of post-MDA surveillance (2007–2010). However, Thai PELF has been challenging sensitive situations of not only border crossings of local people on Thailand-Myanmar border where focal distribution of forest- and forest fringe-related border bancroftian filariasis (BBF) is caused by nocturnally subperiodic Wuchereria bancrofti in local people living in pockets of endemic villages, but also intense cross-border migrations of Mon and Tanintharyi workers from Myanmar to Thailand who harbor nocturnally periodic W. bancrofti microfilaremic infection causing the emergence of imported bancroftian filariasis (IBF). Thus, this paper discusses the apparent issues and problems pertaining to epidemiological surveillance and postgenomic MDA evaluation for 2010–2020 convalescent BBF and IBF. In particular, the population migration linked to fitness of benzimidazole-resistant W. bancrofti population is a topic of interest in this region whether the resistance is associated with pressure of the MDA 2 drugs and the vulnerabilities epidemiologically observed in complex BBF or IBF settings.